2013
DOI: 10.1053/j.gastro.2013.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Evidence From Human and Zebrafish That GPC1 Is a Biliary Atresia Susceptibility Gene

Abstract: BACKGROUND & AIMS Biliary atresia (BA) is a progressive fibroinflammatory disorder of infants involving the extrahepatic and intrahepatic biliary tree. Its etiology is unclear but is believed to involve exposure of a genetically susceptible individual to certain environmental factors. BA occurs exclusively in the neonatal liver, so variants of genes expressed during hepatobiliary development could affect susceptibility. Genome-wide association studies previously identified a potential region of interest at 2q3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
142
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(146 citation statements)
references
References 63 publications
3
142
0
1
Order By: Relevance
“…For example, Jung et al (2015) reported that SHH pathway activation was observed, especially in the cholangiocytes of the peribiliary glands, in human patients with biliary atresia. In pathological studies, some have reported that Hh expression is considerably increased in fibrotic damaged biliary diseases in response to injury (Omenetti et al, 2008;Omenetti and Diehl, 2011;Cui et al, 2013;Hu et al, 2015). It has also been speculated that the SHH signaling pathway regulates the epithelial-mesenchymal transition of cholangiocytes (Omenetti et al, 2008;Jung et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Jung et al (2015) reported that SHH pathway activation was observed, especially in the cholangiocytes of the peribiliary glands, in human patients with biliary atresia. In pathological studies, some have reported that Hh expression is considerably increased in fibrotic damaged biliary diseases in response to injury (Omenetti et al, 2008;Omenetti and Diehl, 2011;Cui et al, 2013;Hu et al, 2015). It has also been speculated that the SHH signaling pathway regulates the epithelial-mesenchymal transition of cholangiocytes (Omenetti et al, 2008;Jung et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been speculated that the SHH signaling pathway regulates the epithelial-mesenchymal transition of cholangiocytes (Omenetti et al, 2008;Jung et al, 2015). The effects of excess SHH signaling encompass defective hepatobiliary ducts in a zebrafish model (Cui et al, 2013;Tang et al, 2016), suggesting that excess SHH signaling can have detrimental effects on the proper development and maintenance of the biliary duct. The current phenotype of reduced SHH signaling in the defective gallbladder might be explained by the distinct roles of SHH signaling during developmental and early pathogenic stages (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…19 A possible association with the gene GPC1 which encodes a glypican 1-a heparan sulfate proteoglycan has been reported. 20 This gene is located on the long arm of chromosome 2 (2q37). This gene is involved in the regulation of the gene Hedgehog and also of inflammation.…”
Section: Epidemiologymentioning
confidence: 99%
“…Another potential causative gene, glypican 1 (GPC1), has garnered attention through genome-wide association studies of DNA copy number variation that identified a potential region of susceptibility to biliary atresia on chromosome 2q37.3, which was replicated in an independent cohort of patients demonstrating heterozygous deletion of GPC1 as the sole gene in this region [66]. Glypican family members are involved in various signaling and developmental pathways in hepatocytes and cholangiocytes, though GPC1 had not been previously associated with liver development or function.…”
Section: Proposed Genetic Etiologies Of Biliary Atresiamentioning
confidence: 99%